Supports from place of delivery and mother in-law were associated with successful exclusive breastfeeding - Ni Wayan Budi Astiti; Ni Putu Widarini; Kadek Tresna Adhi (Universitas Udayana, 2022)
Background and purpose: The 2019 Health Profile of Klungkung District in Bali Province shows that the area of Dawan I Public Health Center has the coverage of exclusive breastfeeding below 80% (72.6%). This study aimed at determining factors associated with the success of exclusive breastfeeding. Methods: This cross-sectional study involved all breastfeeding mothers with children aged 6-11 months old at the time of the data collection who resided in the area of Dawan I Public Health Center. The total number of samples was 105 mothers. Data was obtained from an online survey, using a structured questionnaire. The variables include maternal age, education and working status, parity, birth spacing, mother's attitude and knowledge on breastfeeding, supports from place of delivery and family, including husband and mother-in-law. Data were analyzed using Chi Square Test and Logistic Regression. Results: We found 81.90% of mothers were 20-35 years old, had high education (76.19%) and were working (53.33%). The success rate of exclusive breastfeeding in the working area of Dawan I was only 40.95%. The strongest predictors were the supports from place of delivery and mother-in-law. Mothers who received good supports from the place of delivery had a 4.12 times higher chance (p=0.03; 95%CI: 1.10-15.35) to successful exclusive breastfeeding. Mothers who received good supports from their mother-in-law had a 2.68 times higher chance (p=0.02; 95%CI: 1.13-6.34) to successfully give exclusive breastfeeding to their baby. Conclusion: Supports from place of delivery and mother-in-law are important determinants to be considered in increasing the success rate of exclusive breastfeeding.